The role of institutional ownership in moderating financial distress and sales growth on tax avoidance - Elvin, Muhammad Khahil; Fahria, Rahmasari (Educoretax, 2026)
This study uses a quantitative approach with the aim of empirically testing and analyzing the effect of financial distress and sales growth on tax avoidance, with institutional ownership as a moderating variable. A quantitative approach was chosen because it is able to provide an objective picture of the relationship between variables through measurable and systematic statistical testing. The population in this study includes all companies classified in the mining sub-sector and listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024, with a total of 67 companies. The sample was determined using purposive sampling based on specific criteria, resulting in 46 companies that met the research requirements. With an observation period of three years, this study produced a total of 102 observations that were analyzed. The analysis method used was unbalanced panel data regression, which allowed researchers to combine time series and cross-section data to provide more comprehensive analysis results. Data processing was carried out using STATA software, with a significance level of 5 percent. The results show that financial difficulties have a negative effect on tax avoidance, indicating that companies in difficult financial conditions tend to avoid tax avoidance practices. Meanwhile, sales growth was not found to have an effect on tax avoidance. Furthermore, institutional ownership was found to weaken the negative relationship between financial difficulties and tax avoidance, but it did not moderate the relationship between sales growth and tax avoidance. Keywords: Tax Avoidance, Financial Distress, Sales Growth, institutional ownership